Analysis of acidified feed components containing African swine fever virus. (20th December 2022) - McOrist, Steven; Scott, Peter C.; Jendza, Joshua; Paynter, David; Certoma, Andrea; Izzard, Leonard; Williams, David T.
Abstract: Mitigation of African swine fever (ASF) virus in contaminated feed materials would assist control activities. Various finely-ground pig feed ingredients (5 cereals, 4 plant proteins, 2 animal proteins, 1 oil, 1 compound) were sprayed and mixed thoroughly with a buffered formic acid formulation (0, 1 or 2% vol/vol) to produce a consistent and durable level of formate (1% or 2%) with consistent acidification of cereal ingredients to less than pH 4. No such acidification was noted in other ingredients. Selected representative feed ingredients were further mixed with infectious ASF virus (10 6 TCID50 ) or media alone and incubated for 0, 6, 12, 24, 48, 72 or 168 h. The residual ASF virus at each timepoint was quantified using qPCR and a cell culture based TCID50 assay to determine survivability. Maize, rice bran and compound feed (with or without formate) all reduced infectious ASF virus to levels below the detection threshold of the cell culture assay (10 1.3 TCID50 /mL). A consistent reduction in ASF virus DNA levels was observed by qPCR assay when maize containing ASF virus was mixed with 1% or 2% buffered formic acid. This reduction in viral DNA corresponded to the acidifying pH effect measured. No such reduction in ASF virus DNA levels was noted in non-cereal ingredients containing ASF virus, in which the pH had not been lowered below pH 4 following treatment. Interestingly, residual ASF virus levels in spiked meat/bone meal were greater than control levels, suggesting a buffering effect of that feed ingredient. Highlights: The anti-viral effect of a buffered formic acid formulation was evaluated as an African swine fever (ASF) virus mitigant in feed materials. Spray mixing of cereal ingredients with buffered formic acid produced a consistent and durable level of formate (1% or 2%) and a consistent acidification to less than pH 4. No such acidification was noted in a range of other feed ingredients. Maize, rice bran and a compound feed (with or without formic acid) all reduced infectious ASF virus levels, suggesting that they possess innate virus inactivation properties. ASF virus DNA levels were consistently reduced when cereal maize containing virus was mixed with buffered formic acid. The reduction in ASF viral DNA levels corresponded to the acidifying pH effect measured. In contrast, ASF virus levels were enhanced when meat/bone meal containing ASF virus was mixed with buffered formic acid, indicating a buffering capacity of this ingredient. The practical usage of buffered formic acid to reduce the possible infectivity of feed ingredients in terms of ASF transmission, would be best limited to stored cereals, such as maize.